2015
DOI: 10.3168/jds.2014-8826
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Hepatic progesterone-metabolizing enzymes cytochrome P450 2C and 3A in lactating cows during thermoneutral and heat stress conditions

Abstract: Two experiments were performed to determine the effects of heat stress (HS) and insulin on hepatic mRNA abundance of enzymes responsible for metabolizing progesterone [cytochrome P450 2C and 3A (CYP2C and CYP3A)]. To distinguish the direct effects of HS from decreased dry matter intake, cohorts were pair fed (PF) in thermoneutral conditions to match the intake of the HS cows during both experiments. In the first experiment, multiparous late-lactation Holstein cows (n=12, 305±33 d in milk) housed in climate-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
0
10
0
3
Order By: Relevance
“…Cytochrome P450 ( CYP ) is a superfamily containing a series of genes encoding P450 enzymes and are found in all aerobic eukaryotes and other vertebrates 55 , 56 . In a study on the cytochrome p450 metabolic enzymes in cows under heat stress conditions, the relative abundances of CYP2C and CYP3A were found to be decreased 57 . A study on Symbiodinium under both rapid and gradual thermal stress revealed that up-regulation occurred under gradual heat stress before the maximum temperature was reached, and down-regulation occurred under rapid stress and gradual stress after the maximum temperature was reached 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Cytochrome P450 ( CYP ) is a superfamily containing a series of genes encoding P450 enzymes and are found in all aerobic eukaryotes and other vertebrates 55 , 56 . In a study on the cytochrome p450 metabolic enzymes in cows under heat stress conditions, the relative abundances of CYP2C and CYP3A were found to be decreased 57 . A study on Symbiodinium under both rapid and gradual thermal stress revealed that up-regulation occurred under gradual heat stress before the maximum temperature was reached, and down-regulation occurred under rapid stress and gradual stress after the maximum temperature was reached 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Sequences for TLR4, REL associated protein of NFκB (RELA), acyloxyacyl hydrolase (AOAH), and LBP were designed via NCBI primer blast (https: / / www .ncbi .nlm .nih .gov/ tools/ primer -blast/ ), all spanned at least 1 exon junction, and are detailed in Table 2. Sequences for cytochrome P450 family 2 subfamily C (CYP2C), cytochrome P450 family 3 subfamily A (CYP3A), and ribosomal protein 15 (RPS15) were from McCracken et al (2015). Each set of reactions was performed to include negative controls of water only, as well as cDNA with Mastermix (Thermo Fisher Scientific) and omission of primers.…”
Section: Rna Isolation and Quantitative Reverse-transcription Pcrmentioning
confidence: 99%
“…Another enzyme, cytochrome p450, which is responsible for synthesizing various hormones including progesterone, was upregulated in the TC group embryos. McCracken et al (2015) suggested that adverse reproductive outcomes may be encountered due to heat stress because of the reduction of enzymes essential for progesterone breakdown. The decreased mRNA expression of cytochrome p450 in heat-stressed laying hens may affect their ovaries (Rozenboim et al 2007).…”
Section: Two-dimensional Gel Electrophoresismentioning
confidence: 99%